Weekly paclitaxel plus bevacizumab versus docetaxel as second- or third-line treatment in advanced non-squamous non–small-cell lung cancer: Results of the IFCT-1103 ULTIMATE study. (May 2020) - Cortot, Alexis B.; Audigier-Valette, Clarisse; Molinier, Olivier; Le Moulec, Sylvestre; Barlesi, Fabrice; Zalcman, Gérard; Dumont, Patrick; Pouessel, Damien; Poulet, Claire; Fontaine-Delaruelle, Clara; Hiret, Sandrine; Dixmier, Adrien; et al.
Abstract: Purpose: Second-line chemotherapy regimens have demonstrated poor benefit after failure of platinum-based chemotherapy in advanced non-squamous non–small-cell lung cancer (nsNSCLC). Methods: In this multicentre, open-label phase III trial, patients with advanced nsNSCLC treated with one or two prior lines, including one platinum-based doublet, were centrally randomised to receive 90 mg/m 2 of paclitaxel (D1, D8, D15) plus 10 mg/kg of bevacizumab (D1, D15) every 28 days or docetaxel (75 mg/m 2 ) every 21 days; crossover was allowed after disease progression. Primary end-point was progression-free survival (PFS). ClinicalTrials.gov registration number: NCT01763671 . Results: One hundred sixty six patients were randomised (paclitaxel plus bevacizumab: 111, docetaxel: 55). The median PFS was longer in patients receiving paclitaxel plus bevacizumab than in patients receveing docetaxel [5·4 months versus 3·9 months, adjusted hazard ratio (HR) 0·61 (95% confidence interval [CI]: 0·44–0·86); p = 0·005]. Objective response rates (ORRs) were 22·5% (95% CI: 14·8–30·3) and 5·5% (95% CI: 0·0–11·5) (p = 0·006), respectively. Median overall survivals were similar (adjusted HR 1·17; p = 0·50). Crossover occurred in 21 of 55 (38·2%) docetaxel-treated patients. Grade III-IV adverse events (AEs) were reported in 45·9% and 54·5% of patients treated with paclitaxel and bevacizumab or docetaxel, respectively (p = NS), including neutropenia (19·3% versus 45·4%), neuropathy (8·3% versus 0·0%) and hypertension (7·3% versus 0·0%). Three patients died due to treatment-related AEs (1·8% in each group). Conclusion: Weekly paclitaxel plus bevacizumab as second- or third-line improves PFS and ORR compared with docetaxel in patients with nsNSCLC, with an acceptable safety profile. These results place weekly paclitaxel plus bevacizumab as a valid option in this population. Clinical trials registration number: ClinicalTrials.gov Identifier: NCT01763671 . Highlights: Prognosis of patients with advanced non–small-cell lung cancer (NSCLC) is poor. Few options beyond platinum-based chemo and immunotherapy in non-squamous (ns) NSCLC. Phase III trial of bevacizumab-paclitaxel (wPB) or docetaxel in 2nd/3rd line nsNSCLC. wPB improved progression-free survival and objective response rate. Safety profile was manageable and Quality of Life was preserved with wPB.